Is Hosea Also among the Traumatized?: The Book of Hosea and Trauma Hermeneutics - Kelle, Brad E. (Journal of Biblical literature, 2025)
Trauma readings of the prophetic books of the Hebrew Bible have not typically included the book of Hosea. They have focused predominantly on texts connected with the Babylonian invasions and deportations in the sixth century BCE, especially Jeremiah and Ezekiel. These readings find their background in the broader application of trauma theory to the Hebrew Bible. In this article, I ask whether trauma (as a heuristic framework) might also provide a beneficial lens into the book of Hosea and, if so, what types of trauma, in what ways, and toward what ends. Specific elements in the book of Hosea invite a trauma reading, and recent biblical interpreters have brought trauma hermeneutics to bear on other, previously less-considered prophetic books. Most significantly, newer scholarly treatments of the prophets are incorporating "communal trauma" (or "cultural trauma," "collective trauma," and "social trauma"), with corresponding attention to "transgenerational trauma." Hosea best takes its place in the trauma conversation about the prophetic literature through communal trauma, in which the impact of trauma is not limited to persons; peoples, societies, and cultures can experience trauma in collective ways, and those ways can shape (or reshape) the nature and identity of the community.